Being a Fighter II: 'It's a positive thing around my male friends' (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
In the previous edition of Existential Analysis, some of the initial findings of a small-scale qualitative study were presented. Those findings related particularly to the ways in which the participants understood themselves. This paper presents further findings, and those described here concern themselves with the relational characteristics of those that identify as a fighter.